Evaluation of tissue displacement in posterior palatal seal area with different impression techniques with varying palatal forms - Abdul Khafoor, Mayada Q; Ibrahim, Rafah A; Al-abdulla, Ilham H (Journal of Baghdad College of Dentistry, 2013)
Background: This study was designed to measure the displacement pattern of posterior palatal seal (pps) area in different forms of the palate and with different impression techniques. Materials and method: This study was used to measure the displacement pattern of (pps)in different palatal shapes by using different impression materials Korrecta wax No.4,Green compound and design of House for pps for each palatal forms by using a 3D Scanner of CAD/CAM and measuring the distance between 2 points in pps area by using Caural Threw. Result: The results show highly significant differences between these techniques and the control group (impression with light body) Conclusion: The physiological impression technique of pps with Korecta wax no.4 and design of House for each palatal forms give less displacement than the physiological impression with green compound.